The promise of experiential education in teacher education: transforming teacher beliefs and practices. Issue 3 (3rd July 2019) - Glazier, Jocelyn; Bean, Amanda
Abstract: Building from the theories of Dewey and Kolb and Fry, we sought to examine the impact of experiential education in teacher education on teacher beliefs and practices. The teacher education model described in this article sets out to challenge the seduction of the apprenticeship of observation and create an opportunity for in-service teachers to re-imagine their teaching in concrete and transformative ways. Immersed in a weeklong experiential residency in either the mountains or at a local environmental education farm, the teachers in the study were challenged physically, intellectually, socially, and emotionally in and through the experience. The experiential work ultimately led to changes in teacher participants' beliefs and practices related to teacher and student roles and potentialities. Although challenges exist for this type of practice in K-12 classrooms and in teacher education, experiential education has a significant potential to change the way teachers think about and act in their practice.